World agricultural products market and the positions of China, Belarus and Russia in it - Wang , Yaotian (Journal of the Belarusian State University. Economics, 2024)
The positions of China, Belarus and Russia in the world market of agricultural products are analysed in comparison with the positions of the leaders of foreign trade of agricultural products (the EU countries, USA and Brazil). The change in the competitive positions of the states is tracked using the author’s proposed model for analysing export-import operations of the countries in the world market. The article reveals the rapid growth of international competitive positions of the agrocultural sectors of China, Belarus and Russia, and identifies the reasons for this growth. The priority directions of development of their mutual foreign trade in agricultural products are outlined.